Problems of the Formulation of Asset Forfeiture Resulting from Corruption Crimes: A Comparative and Conceptual Study - Sry Karina Br. Sinuhaji; Mar'ie Mahfudz Harahap (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2024)
Corruption in Indonesia has long been a severe transnational issue requiring appropriate handling. Although Law No. 31 of 1999 and Law No. 20 of 2001 on the Eradication of Corruption have provided a legal basis for combating corruption, weaknesses remain in their implementation. This study aims to evaluate the effectiveness of these laws by employing a legislative approach and analyzing the opinions of scholars. The primary focus of this research is on asset confiscation resulting from corruption, as regulated by the Anti-Corruption Law, which serves as a key instrument in combating corruption. The findings indicate that unclear legal norms and weak coordination among law enforcement agencies still hinder the implementation of asset confiscation. The conclusion of this study emphasizes the need for regulatory improvements and enhanced coordination among institutions to maximize the effectiveness of asset confiscation in efforts to eradicate corruption in Indonesia